KAJIAN TEOLOGIS TENTANG PRINSIP MEMBERI MENURUT 1 RAJA-RAJA 17:7-24 - Monei, Meliakim; Kristiana, Pestaria Happy (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2023)
This research talks about the principle of giving in theological studies based on the book of 1 Kings 17:7-24. Giving offerings to God is a sign of gratitude for all the blessings that God has given. Likewise, giving to fellow humans is a form of social concern and generosity that believers have. Don't give because you have more, but because you have compassion so you want to share with others. Data collection techniques were carried out by means of interviews, observation and examination of documents to the extent that could be obtained during the research. The purpose of this research is to explain to members of the East Nabire Classis Pentecostal Church in Papua (GPDP) congregation. As a result of this research, it was found based on 1 Kings 17:7-24 that the principles of giving are as follows; Giving to share, Motivation in giving, Giving from lack, Giving sincerely and honestly, Having generosity, Giving with faith. The conclusion of the research is that giving is evidence of obedience and belief in God's word.